2019
DOI: 10.24331/ijere.573871
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Jigsaw Type Cooperative Learning Model to Improve Economics Learning Results

Abstract: This study aims to determine the application of the Jigsaw type cooperative learning model to students and whether or not there is an increase in learning outcomes in economic subjects. Jigsaw cooperative learning is learning that focuses on discussion by groups of experts and groups of origin. Discussions conducted by students aim to understand the material being studied. The problem posed is about economic subject matter. This research is a classroom action research consisting of two cycles. This classroom a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 1 publication
0
6
0
2
Order By: Relevance
“…as Jig-saw (Costouros, 2020;Rohmat et al, 2019), peer instruction (Mazur & Hilborn, 1997), Think-Pair-Share (Lyman, 1981), Round Robin (Delina & Refelita, 2021) and Numbered Heads (Zarti & Khairani, 2020). During this stage, the teacher asks questions that guide the development and allow students to know if they are working in the right direction; these questions are asked directly or through queries via Mentimeter.…”
Section: The Solution: the Methodological Shift Towards Flmentioning
confidence: 99%
“…as Jig-saw (Costouros, 2020;Rohmat et al, 2019), peer instruction (Mazur & Hilborn, 1997), Think-Pair-Share (Lyman, 1981), Round Robin (Delina & Refelita, 2021) and Numbered Heads (Zarti & Khairani, 2020). During this stage, the teacher asks questions that guide the development and allow students to know if they are working in the right direction; these questions are asked directly or through queries via Mentimeter.…”
Section: The Solution: the Methodological Shift Towards Flmentioning
confidence: 99%
“…Melalui pemaparan data diatas, diperoleh bahwa model pembelajaran kooperatif tipe jigsaw mampu memberikan peningkatan hasil belajar. Rohmat (2019) mengungkapkan bahwa model pembelajaran kooperatif jigsaw memberikan peningkatan pengalaman belajar dan hasil belajar peserta didik. Model tersebut mampu melatih kemandirian peserta didik dan memperbaiki hasil belajar peserta didik (Saputra at al., 2019).…”
Section: Siklus IIunclassified
“…Few research papers have been published on CL in economy but those researches have been carried out in senior high school students (Rohmat et al, 2019) where the application of a CL tool, jigsaw type, improved the learning outcomes. In a recent paper where the researchers applied the jigsaw type of CL to students of cycle I and cycle II of accounting, they found that the jigsaw did not succeed in the student of cycle I, but the jigsaw type of CL succeeded in students of cycle II (Rokhmah & Subroto, 2019) It can be concluded that despite of the importance of the subject of economy in the curriculum of secondary education, only one empirical paper was found in our review.…”
Section: Discusionmentioning
confidence: 99%
“…The most notable result from our review on Cooperative Learning in the subject of economy in secondary education is the near absence of empirical studies. Only one paper was identified (Rokhmah & Subroto, 2019) through the reference list of another (Rohmat et al, 2019).…”
Section: Discusionmentioning
confidence: 99%
See 1 more Smart Citation